India's energy security - Singh, Bhupendra Kumar (New Delhi, 2010)
Energy is the lifeline for economic development. India is diverse in its energy endowments and requirements. Energy demand is increasing day-by-day due to increase in population and per capita income. India imports about seventy per cent of its energy needs, out of which seventy two percent comes from the Persian Gulf. However, this region is volatile. Therefore India is diversifying its energy supply. This book tries to evaluate the importance of Persian Gulf in spite of diversification. It also analyses the changing dynamics of India's energy security like inherent desire of energy cooperation with big competitor like China, playing active role in International Energy Organizations, enhancing energy efficiency and promoting renewable energy to combat the growing concern of climate change.
Keywords: Energy Security-India